2018
DOI: 10.1515/psr-2017-0125
|View full text |Cite
|
Sign up to set email alerts
|

Selenium– and tellurium–nitrogen reagents

Abstract: Abstract The reactivity of the chalcogen–nitrogen bond toward main-group element or transition-metal halides, as well as electrophilic and nucleophilic reagents, is the source of a variety of applications of Se–N and Te–N compounds in both inorganic or organic chemistry. The thermal lability of Se–N compounds also engenders useful transformations including the formation of radicals via homolytic Se–N bond cleavage. These aspects of Se–N and Te–N chemistry will be illustrated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
(104 reference statements)
0
1
0
Order By: Relevance
“…In recent years, there has been great interest in studying organo-tellurium compounds containing azomethane group due to the high stability and various applications of these compounds [3,4]. The applications of organotellurium compounds have been reported in several fields [4][5][6][7][8]. Past research reported using organotellurium compounds as antioxidant agents [5,9,10], polymerization catalysts [11][12][13], antitumor and pharmaceutical agents [5,14,15], organic superconductors [3,7], synthetic intermediate [4], and ligands with many transition metal ions [3,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been great interest in studying organo-tellurium compounds containing azomethane group due to the high stability and various applications of these compounds [3,4]. The applications of organotellurium compounds have been reported in several fields [4][5][6][7][8]. Past research reported using organotellurium compounds as antioxidant agents [5,9,10], polymerization catalysts [11][12][13], antitumor and pharmaceutical agents [5,14,15], organic superconductors [3,7], synthetic intermediate [4], and ligands with many transition metal ions [3,16,17].…”
Section: Introductionmentioning
confidence: 99%